2018
DOI: 10.1017/s0950268818001693
|View full text |Cite
|
Sign up to set email alerts
|

Genotype replacement of the human parainfluenza virus type 2 in Croatia between 2011 and 2017 – the role of neutralising antibodies

Abstract: Previously we reported on the HPIV2 genotype distribution in Croatia 2011-2014. Here we expand this period up to 2017 and confirm that G1a genotype has replaced G3 genotype from the period 2011-2014. Our hypothesis was that the G1a-to-G3 genotype replacement is an antibody-driven event. A cross-neutralisation with anti-HPIV2 sera specific for either G1a or G3 genotype revealed the presence of genotype-specific antigenic determinants. By the profound, in silico analyses three potential B cell epitopic regions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Ours is the first study to provide HN gene sequences including phylogenetic characterization for HPIV types 1–4 from Germany, and, to our knowledge, it is one of only five studies providing HN gene sequence data from HPIV circulating in Europe [ 10 , 11 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ours is the first study to provide HN gene sequences including phylogenetic characterization for HPIV types 1–4 from Germany, and, to our knowledge, it is one of only five studies providing HN gene sequence data from HPIV circulating in Europe [ 10 , 11 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clusters G1 and G2 constituted the first cluster identified by Terrier et al, while Clusters G3 and G4 constituted the second cluster identified by Terrier et al, respectively. The molecular characterization of additional HPIV-2 isolates collected between 2011 and 2017 led to the determination of more HPIV-2 sequences, which were categorized into the predefined clusters G1 and G3 [ 10 , 39 ]. Cross-neutralization activity between Clusters G1 and G3 was low, indicating the existence of distinct genotype-specific antigenic determinants [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analyses showed that different genetic lineages of HPIV3 in sub-cluster C3 co-circulated in China, with C3f as the dominant lineage according to the HN gene sequence. Based on the phylogenetic tree of the HN gene of HPIV2 in a previous study (Santak et al, 2018), G1c was defined as a new sub-cluster in this study. Two HPIV4 sequences belonged to cluster 4A, and cluster 4B was not found in this study.…”
Section: Discussionmentioning
confidence: 99%